Analisis Kebutuhan Jumlah Tenaga Kerja untuk Memenuhi Permintaan Produk Kertas pada PT X - Putra, Aditya Rafly Syah; Herlina, Herlina (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
PT This research focuses on the paper production section of PM (Paper Machine) one. The problem of this research is to analyze whether the paper production section at PM (Paper Machine) one is experiencing a shortage of workers. In this case, it means that PT X has never found the ideal number of workers. Therefore, the Work Load Analysis (WLA) method is used in this research. The results show that the production of paper products is 3,350 tons, with a manufacturing time of 99.42 minutes per roll on PM (Paper Machine) one requiring 34 workers, so an additional 15 workers are needed. Then if the company does overtime for 19 workers the company will only incur more costs. less than increasing the number of workers. In addition, it is better if the company continues to use 19 workers with overtime hours because labor costs will become too high if they increase the number of workers.